Load reduction characteristics of swept blade for 15 MW wind turbine - Ma, Lu; Li, Yijia; Zhou, Le; Guo, Hao; Shen, Xin; Du, Zhaohui (Frontiers in Energy Research, 2025)
IntroductionSwept blades can achieve effective load reduction, thereby improving the operational performance of wind turbines. To investigate the impact of hundred-meter-level swept blades on the load characteristics of wind turbines, this paper takes the IEA-15 MW wind turbine as the subject.MethodsBased on the free-wake lifting line theory model and the geometrically exact beam theory model, the load characteristics of straight blades and swept blades under rated conditions are compared.Results and discussionThe results show that swept blades undergo greater torsional deflection, thereby reducing the effective angle of attack of the blades and achieving load reduction. The influence of different sweep parameters on load characteristics is also discussed. The study finds that the load reduction effects of the sweep starting point and sweep index are similar, while the load reduction effect of the sweep displacement is the most significant, and it becomes more pronounced as the sweep displacement increases. Additionally, under yaw conditions, as the sweep displacement increases, the gradually increasing torsional deflection and the gradually decreasing amplitude of the flapwise speed fluctuation lead to a downward trend in both the mean and fluctuation amplitude of the angle of attack.